2018
DOI: 10.3892/ijmm.2018.3691
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of dehydrocostuslactone on rat hippocampal slice injury induced by oxygen‑glucose deprivation/reoxygenation

Abstract: The present study aimed to investigate the protective effects of dehydrocostuslactone (DHL) against rat hippocampal slice injury caused by oxygen‑glucose deprivation/reoxygenation (OGD/R). Rat hippocampal slice injury was induced by OGD/R in vitro, and the degree of injury was evaluated through a lactate dehydrogenase (LDH) assay and 2,3,5‑triphenyltetrazolium chloride (TTC) staining. The protein expression levels of B‑cell lymphoma-2 (Bcl‑2), Bcl‑2‑associated X protein (Bax), cytochrome c (cyt‑c), apoptotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The favorable effect of the phenolic and flavonoids compounds in S. lappa treatment on blood cells production could be responsible for the adjustment of the different leukocytes count [37]. In addition, the anti-apoptotic activity of S. lappa detected here and in other types of cells in earlier studies [72,73] could partly share in suppressing neutrophil proliferation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The favorable effect of the phenolic and flavonoids compounds in S. lappa treatment on blood cells production could be responsible for the adjustment of the different leukocytes count [37]. In addition, the anti-apoptotic activity of S. lappa detected here and in other types of cells in earlier studies [72,73] could partly share in suppressing neutrophil proliferation.…”
Section: Discussionmentioning
confidence: 70%
“…However, it seems that S. lappa has a different mode of action toward normal cells. For instance, in the study of Zhao et al [73], S. lappa's main bioactives significantly reduced the Caspase-dependent apoptotic pathway in neuronal cells, probably linked to the free radical scavenging activity. Besides, other natural products showed selective apoptotic activity [105,106].…”
Section: Discussionmentioning
confidence: 96%
“…The balanced redox effect of ginsenoside Rd may contribute to the improvement of cerebral injury symptoms (Ye et al, 2011a). Further evidence showed that Rd could improve mitochondrial respiratory function and increase ATP production by reducing ROS production, thereby maintaining MMP and inhibiting neuronal apoptosis (Ye et al, 2011b), which was similar to dehydrocostuslactone's protection of rat hippocampal slices from OGD/R-induced damage (Zhao et al, 2018a). Astragalosides IV may maintain mitochondrial function and inhibit OGD/R-induced cortical neuronal apoptosis by regulating PKA/CREB signaling pathway (Xue et al, 2019).…”
Section: Monomers and Molecular Mechanisms In Regulating Mptp Opennesmentioning
confidence: 94%
“…Additionally, picroside II attenuated cerebral I/R injury by inhibiting EndoG release from the mitochondria into the cytoplasm ( Li et al, 2018 ) Similarly, baicalein treatment decreased cerebral I/R injury by inhibiting nuclear translocation of AIF in cerebral I/R rats ( Li et al, 2020 ). Many in vivo ( Zhang et al, 2017 ; Zhao et al, 2018b ; Cheng et al, 2019 ; Yin et al, 2020 ; Li et al, 2021 ; Zhang et al, 2021 ; Li et al, 2022b ; Peng et al, 2022 ) and in vitro ( Zhao et al, 2018a ; Feng et al, 2018 ; Liu et al, 2018 ) studies have shown that TCM compounds (e.g., curcumin, artemether, ferulic acid, artemisinin, rhein, astragaloside IV, l-borneol, calenduloside E, ginkgolide K, dehydrocostus lactone, and icariside II) exert protective effects in MCAO animal models or OGD/R cell models by inhibiting BAX/BCL2, caspase-9, caspase-3, cleaved caspase-3, caspase-8, Cyt-c, Bid, Apaf-1, Bad, and p53 ( Figure 4 ).…”
Section: Progress In Ischemic Stroke Prevention and Treatment Using T...mentioning
confidence: 99%